University Quasi Justice System and Underreporting of Female Sexual Harassment in Selected Universities in Edo State, Nigeria - Osunde, Isoken Linda (NIU Journal of Social Sciences; Vol 11 No 1 (2025): NIU Journal of Social Sciences, Vol. 11 No. 1, March 2025, 2025)
Sexual harassment of female student in Universities has become an agonizing contemporary issue in all Universities of the world Particular in Nigeria, as it is evidenced by the incessant cases of female sexual harassment in Nigerian Universities. It is against this background, that this study sought to examine the justice system and underreporting of female sexual harassment in selected Universities in Edo State. The deterrence theory was used to explain the topic under investigation. The explanatory research design was used with the aid of the qualitative technique to gather data for the study. 15 key informant interviews and 30 in-depth interviews were conducted to gather data from the study area which comprised; University of Benin, Benin city, Ambrose Alli University, Ekpoma, and Igbinedion University, Okada. The data gathered were contently analysed. The study revealed that although, there are social control mechanisms for addressing female sexual harassment in these Universities, but their effectiveness leaves much to be desired as the quasi justice system actors within these Universities more often than not pay lip services to enforcement. The study recommends a thorough overhauling of the University quasi Justice system and its social control mechanisms for addressing the harassment of female students sexually and the encouragement of victims to speak out. Keywords: Quasi Justice System, Sexual Harassment, Underreporting, University, Victims